The effect of laterally positioned flap-revised technique and 24% ethylenediaminetetraacetic acid root conditioning on root coverage: A case report - Jagmohan Singh; Vipin Bharti (Saudi Dental Journal)
Complete root coverage is considered the true goal of treatment of gingival recession defects because only complete coverage assures recovery from the hypersensitivity and esthetic defects associated with recession areas. Previous studies have shown that the laterally positioned flap (LPF) technique or root surface biomodification yields a higher percentage of complete root coverage upon gingival recession treatment. This article highlights the use of the laterally positioned pedicle flap-revised technique (LPFRT) as a modification of the LPF technique, along with 24% EDTA gel as a root surface biomodification agent, in the management of localized gingival recession defects. Clinical examination revealed a Miller class II recession defect on the buccal aspect of the lower right central incisor, as well as the presence of aberrant frenum pull adjacent to the recession defect. The LPFRT, together with 24% EDTA gel, was speculated to cover the gingival recession defect. The frenectomy, along with periosteal fenestration, was planned simultaneously with LPFRT. After 6 months of therapy, the clinical condition was stable with complete root coverage and satisfactory healing of the gingival tissues at both the donor and recipient sites with no signs of inflammation. Keywords: Ethylenediaminetetraacetic acid, Esthetics, Gingival recession, Pedicled flap, Root coverage